2019
DOI: 10.18203/issn.2455-4510.intjresorthop20191444
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric forearm refractures- management and outcome: a prospective study

Abstract: <p class="abstract"><strong>Background:</strong> Forearm fractures are one of the commonest injuries accounting for 40% of paediatric fractures with a refracture rate of nearly 5%. Forearm refractures are increasing probably due to poor bone mineralization as a result of decreased physical activity, Vitamin D deficiency. These are treated by conservative measures with closed reduction and casting or by surgical fixation with flexible nails or plates. There are no definitive guidelines for man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In a similar study comprising of 32 patients Kuloor SB et al, found that 56% of the patients had union at 6 weeks and all patients had union at 8 weeks follow up visit. These findings were similar to the findings of our study 18. Finally in our study functional outcome as assessed on the basis of Quick DASH score showed that 42 (70%) patients had excellent functional outcome whereas 9 (15%) patients had good functional outcome.…”
supporting
confidence: 92%
“…In a similar study comprising of 32 patients Kuloor SB et al, found that 56% of the patients had union at 6 weeks and all patients had union at 8 weeks follow up visit. These findings were similar to the findings of our study 18. Finally in our study functional outcome as assessed on the basis of Quick DASH score showed that 42 (70%) patients had excellent functional outcome whereas 9 (15%) patients had good functional outcome.…”
supporting
confidence: 92%
“…There are studies that have focused solely on the risk of refracture in the forearm, which the current study demonstrates to be the segment most commonly affected by refractures. 4,7,11,15 Bould and Bannister 7 reported a rate of 4.9% refractures in a study of 768 children with forearm fractures, while Kuloor et al 11 reported similar findings of a refracture rate of 4.7% in 610 forearm fractures. In 2021, Soumekh et al 15 studied refracture rates in 426 diaphyseal forearm fractures with different immobilization regimens, and found that they were 1.7% to 5%.…”
Section: Discussionmentioning
confidence: 93%
“…Although many studies have described the epidemiology of paediatric fractures, only a few have examined the incidence of refractures. 2,[6][7][8][9][10][11][12][13][14][15][16] These studies of refractures in children are retrospectively reviewed cohorts of a specific part of the body, most commonly focusing on the forearm. [7][8][9][10][11][12][13][14][15] To the best of our knowledge, no previous study has described refractures in relation to all occurring primary fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation